Biographical dictionary of enslaved Black people in the Maritimes - Whitfield, Harvey Amani, 1974- (Studies in Atlantic Canada history., 2022)
"This biographical dictionary recovers the stories and illuminates the lives of enslaved Black people in the Maritimes."--